A Comment on "The Effects of Import Competition on Unionization" - Matthew Kutam; Jonathan Roth (Institute for Replication (I4R), 2024)
We replicate the primary results from Ahlquist and Downey (2023, AD), who examine the effects of Chinese import competition on both industryand state-level unionization in the US. We are able to directly replicate the main results in AD Tables 1 and 2. We consider two main extensions. First, we consider a version of the industry-level analysis that uses log union share instead of the level. We again find a significant negative effect on union share, although the effect on log union share explains a larger fraction of the total drop between 1990 and 2014. Second, for the state-level results, we segment the manufacturing employment share into unionized and nonunionized manufacturing. We find that at the state level, the impacts of import exposure are concentrated entirely in non-union manufacturing. The estimated impact on union manufacturing employment is actually positive, but small and statistically insignificant. This is contrast with the results at the industry level where the effects are negative for both union and non-union manufacturing and larger in magnitude for union manufacturing.
Keywords: 330